1998
DOI: 10.1128/aem.64.10.3683-3689.1998
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Relative Abundance of Different Bacteroides and Prevotella Ribotypes in Gut Samples by Restriction Enzyme Profiling of PCR-Amplified 16S rRNA Gene Sequences

Abstract: We describe an approach for determining the genetic composition ofBacteroides and Prevotellapopulations in gut contents based on selective amplification of 16S rRNA gene sequences (rDNA) followed by cleavage of the amplified material with restriction enzymes. The relative contributions of different ribotypes to total Bacteroides andPrevotella 16S rDNA are estimated after end labelling of one of the PCR primers, and the contribution ofBacteroides and Prevotellasequences to total eubacterial 16S rDNA is estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…Taking into account the fact that, when using bacterial primers, only the most abundant species are detected, two sets of group specific primers were applied to monitor the stabilisation period. The Bacteroides/Prevotella group comprises the most dominant anaerobic bacteria present in the intestinal tract [34]. Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the fact that, when using bacterial primers, only the most abundant species are detected, two sets of group specific primers were applied to monitor the stabilisation period. The Bacteroides/Prevotella group comprises the most dominant anaerobic bacteria present in the intestinal tract [34]. Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…(2) 1 0 ; 94°C/1 0 ; 56°C/2 0 ; 72°C (35Â) (3) 10 0 ; 72°C FD1 [34] (1) 5 0 ; 94°C Bacteroides/Prevotella RbacPre (2) 2 0 ; 94°C/30 00 ; 60°C/2 0 ; 72°C (30Â) (3) 10 0 72°C Fig. 1.…”
Section: Primersmentioning
confidence: 99%
“…Culture-based studies showed that Prevotella strains account for 60% of total cultivable bacteria from the rumen of cows (Van Gylswyk, 1990). Based on restriction enzyme profiling of PCR-amplified 16S rRNA gene sequences from rumen samples, Wood et al (1998) reported that the relative abundance of rumen Prevotella/Bacteroides ribotypes in the total eubacterial 16S rRNA gene could range from 12% to 62%. They also demonstrated that the most abundant Prevotella ribotype was related to very few cultured strains, suggesting underrepresentation of certain members of the genus by cultured strains.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that fecal members of the phylum Bacteroidetes are ecologically diverse, numerically important members of the intestinal microbial communities and exhibit some host specificity (Salyers, 1984;Gherna & Woese, 1992;Wood et al, 1998;Boone & Castenholz, 2001;Daly et al, 2001;Leser et al, 2001;Hold et al, 2002). Recently, Bernhard & Field (2000a, b) developed PCR-based, 16S rRNA gene assays targeting Bacteroidetes which were capable of distinguishing between human and ruminant sources (Bernhard & Field, 2000a, b;Bernhard et al, 2003;Field et al, 2003).…”
Section: Introductionmentioning
confidence: 99%